What happens to bone mineral density, strength and body composition of ex-elite female volleyball players: A cross sectional study - Küçükkubas, N.; Korkusuz, F. (Science & Sports, 2019)
Background and aim: Bone Mineral Density (BMD) and effects of exercise have been extensively studied for prevention and treatment. However, little is known as what happens to body composition, bone, and strength in a long period of time after quitting. The aim of this study was to compare BMD of ex-elite volleyball players (Ex-eVP) and sedentary women (SW) at the age of 40 and over regarding to their body composition, muscle strength. Materials and methods: Thirty-three Ex-eVP and 33 sedentary women SW volunteers at the ages of 40 and over participated in the present study. BMD was measured by Dual Energy X-Ray Absorptiometry (DXA, Lunar Model DPX). Body composition compartments were obtained from total body scans. Takei Physical Fitness Test Dynamometers were used to measure subjects` leg, back and hand grip static strength. Results: Findings revealed that all sites of BMD values of ex-eVP (except for distal forearm values) were higher than that of SW. Body composition were examined in part, body weight of ex-eVP (67.9±8.3kg) were not significantly higher than SW (65.2±9.2kg), and lean body mass were significantly higher (41.59±4.96 P<0.01) than SW (37.80±3.46) in their older ages. Gained bone mass remained higher significantly (P<0.01) at major sites for total body scan of leg and regional body scan of L2-4, in Ex-eVP (1.247±0.170 and 1.217±0.118 respectively) than SW (1.140±0.132 and 1.144±0.092 respectively) (Fig. 2). There was no significant difference in any of the left or right/dominant or non-dominant forearm and hip BMD values. Ex-eVP's static back, leg, left hand grip and right-hand grip strength (64.7±11.7; 107.6±27.2; 28.0±3.4 P<0.001 and 29.3±4.3 P<0.01 respectively) were significantly higher than that of SW (51.8±12.1; 81.4±25.0; 24.2±3.6 P<0.001 and 25.6±4.3 P<0.01 respectively) (Fig. 3). There was a significant but low relationship between Total Body BMD with FW for ex-eVP and total subjects (r=0.369 and 0.311 P<0.05 respectively). Conclusion: Playing volleyball at young ages helps to prevent osteoporosis and/or reverse bone loss, due to the possibilities of having less age-related bone loss and/or/both achieved higher peak bone mass than that of the sedentaries, notwithstanding age-related bone loss.